The Need for Speed! Experimenting with “Speed Training” in the Scientific/Technical Translation Classroom - Bowker, Lynne (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2016)
Most translator training courses focus on encouraging students to reflect fully, to analyze deeply, and to weigh options carefully. However, as they near the end of a translation program, they must also begin preparing for the workplace, where they will need to translate on tight deadlines. Therefore, the addition of authentic and situated learning that tests and improves students’ translation skills under time pressure makes sense. This article describes a pilot project in speed training that took place in a scientific/technical translation course taught during the final semester of a translation program at the University of Ottawa. As part of the experiment, 29 students participated in nine speed training exercises on texts dealing with various scientific/technical subjects. Gamification was introduced as a pedagogical strategy to engage the students during the speed training. The resulting translations were analyzed, the students’ progress was charted over the course of the semester, and they were surveyed about their experience. Though not scientifically valid, the results nonetheless suggest that students can benefit from speed training. Participants reported feeling more confident in their abilities and judgment and less likely to rely blindly on information resources.